Geometric calibration for a SPECT system dedicated to breast imaging - 武丽伟 曹学香 王璐 黄先超 柴培 贠明凯 张玉包 张龙 单保慈 魏龙 (Chinese physics C, 2012)
Geometric calibration is critical to the accurate SPECT reconstruction. In this paper, a geometric calibration method was developed for a dedicated breast SPECT system with a tilted parallel beam （TPB） orbit. The acquisition geometry of the breast SPECT was firstly characterized. And then its projection model was established based on the acquisition geometry. Finally, the calibration results were obtained using a nonlinear optimization method that fitted the measured projections to the model. Monte Carlo data of the breast SPECT were used to verify the calibration method. Simulation results showed that the geometric parameters with reasonable accuracy could be obtained by the proposed method.